CXCL9 and CXCL10 support the exacerbated humoral response in recovered COVID-19 patients who developed acute respiratory distress syndrome by promoting plasma cell differentiation, whereas CXCL9 also induces CD40L and CXCR3 upregulation on T helper cells - Quiroga, Romina; Sanhueza, Sergio; Sepúlveda, Catalina; Antilef, Bárbara; Muñoz, Camila; Cabrera, Camilo; Fraga, Marco; Llerena, Faryd; Lamperti, Liliana; Barría, María Inés; Colombo, Alicia; Labarca, Gonzalo; et al. (Frontiers in Immunology, 2025)
BackgroundSevere COVID-19 is frequently associated with acute respiratory distress syndrome (ARDS) and prolonged pulmonary sequelae. Persistent immune activation, including dysregulated B cell responses and increased proinflammatory chemokines, has been linked to the post-acute sequelae of SARS-CoV-2 infection. However, the mechanisms linking these factors remain poorly defined.MethodsSixty patients were studied four months after acute COVID-19, including 34 who developed ARDS, 26 who did not develop ARDS, and 12 healthy controls. Clinical, computed tomography scan (CT), and diffusion capacity of the lungs for carbon monoxide (DLCOc) assessments were performed. Anti-SARS-CoV-2 IgM/IgG levels were quantified, circulating B cell subsets were characterized, and circulating cytokines and chemokines were measured. CXCR3 expression on B cells was analyzed by spectral flow cytometry. In vitro assays were performed to evaluate the effects of CXCL9 and CXCL10 on B cell activation, plasma cell differentiation, IgG production, and CD40L expression on CD4+ T cells. Associations between immunological markers and pulmonary sequelae were assessed.ResultsIgG, but not IgM, levels were significantly higher in patients with ARDS than in patients without ARDS. Both COVID-19 groups showed a reduction in CD19+CD20+ B cells and an increase in plasmablasts compared to controls. Serum levels of CXCL9 and CXCL10, but not other cytokines, positively correlated with IgG levels. In vitro, CXCL9 increased CD86 expression on B cells, while both chemokines promoted plasma cell differentiation (CD27+CD38+, CD138+) and increased total IgG secretion. CXCL9 also increased the expression of CXCR3 and CD40L on activated CD4+ T cells. Clinically, patients with combined CT abnormalities and reduced DLCO had the highest levels of IgG, CXCL9, and CXCL10.ConclusionFour months after COVID-19, patients with prior ARDS and persistent pulmonary sequelae exhibit sustained elevations of anti-SARS-CoV-2 IgG and chemokines CXCL9 and CXCL10. Both chemokines directly enhance B cell differentiation into IgG-secreting plasma cells in vitro, while CXCL9 also increases CD4+ T cell help, suggesting a mechanistic link between chronic inflammation, increased humoral responses, and long-term lung impairment. Targeting CXCL9/CXCL10–CXCR3 signaling could offer therapeutic potential to mitigate post-COVID pulmonary complications.